2022
DOI: 10.1101/2022.03.18.484902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role of Lck annular lipids in the steady upkeep of active Lck in T cells

Abstract: Theoretical work suggests that collective spatiotemporal behaviour of integral membrane proteins (IMPs) can be modulated by annular lipids sheathing their hydrophobic moiety. Here, we present evidence for this prediction in a natural membrane by investigating the mechanism that maintains steady amount of active isoform of Lck kinase (LckA) by Lck trans-autophosphorylation offset by the phosphatase CD45. We gauged experimental suitability by quantitation of CD45 and LckA subcellular localisation, LckA generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…Upon binding to the membrane, we show that the full-length Lck is surrounded by a pool of negatively charged lipid headgroups creating an anionic environment, whereas it is also observed that the TCR-CD3 cytoplasmic tails maintain an anionic lipid environment 18 . This sheds light on the potential significance of lipids during TCR-Lck association 19 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Upon binding to the membrane, we show that the full-length Lck is surrounded by a pool of negatively charged lipid headgroups creating an anionic environment, whereas it is also observed that the TCR-CD3 cytoplasmic tails maintain an anionic lipid environment 18 . This sheds light on the potential significance of lipids during TCR-Lck association 19 .…”
Section: Discussionmentioning
confidence: 78%
“…Lck was also shown to possess high affinity for PIP lipids 16 and its clustering is driven by their open conformational state 6 . However, lateral interactions of Lck molecules may also include other Lck isoforms as suggested by a recent study 19 . Nevertheless, it is important to understand how the open and closed states of Lck interact with the membrane in molecular detail.…”
Section: Introductionmentioning
confidence: 94%